The recognition mode between hsRBFA and mitoribosome 12S rRNA during mitoribosomal biogenesis. Issue 3 (9th January 2023) - Zhou, Wanwan; Liu, Xiaodan; Lv, Mengqi; Shi, Yunyu; Zhang, Liang
Abstract: Eukaryotes contain two sets of genomes: the nuclear genome and the mitochondrial genome. The mitochondrial genome transcripts 13 mRNAs that encode 13 essential proteins for the oxidative phosphorylation complex, 2 rRNAs (12s rRNA and 16s rRNA), and 22 tRNAs. The proper assembly and maturation of the mitochondrial ribosome (mitoribosome) are critical for the translation of the 13 key proteins and the function of the mitochondrion. Human ribosome-binding factor A (hsRBFA) is a mitoribosome assembly factor that binds with helix 28, helix 44 and helix 45 of 12S rRNA and facilitates the transcriptional modification of 12S rRNA during the mitoribosomal biogenesis. Previous research mentioned that the malfunction of hsRBFA will induce the instability of mitoribosomes and affect the function of mitochondria, but the mechanisms underlying the interaction between hsRBFA and 12S rRNA and its influence on mitochondrial function are still unknown. In this study, we found that hsRBFA binds with double strain RNA (dsRNA) through its whole N-terminus (Nt) instead of the KH-like domain alone, which is different from the other homologous. Furthermore, we mapped the key residues that affected the RNA binding and maturation of mitoribosomes in vitro . Finally, we investigated how these residues affect mitochondrial functions in detail and systematically.